The management of foreign exchange risk by listed companies: an empirical study - Mogaladi, George Tshegofatso (Research of GSB, 2017)
This study explored the foreign exchange risk management practices by JSE-listed companies, specifically non-financial companies. The investigation was based on the experienced practices in 2015. A web-based survey was used to source data from the population and yielded a 37% response rate. Transactional risk is the most prioritised form of foreign exchange exposure. Surprisingly, economic exposure is also highly regarded by JSE non-financial firms. Translational risk is the least prioritised form of foreign exchange risk. There is a significant statistical relationship between the frequency at which firms manage economic risk, and the industry to which they belong. Consistent with the prescriptive theory, the study found that a significant majority of firms used internal or operational hedging techniques in combination with financial derivatives. Netting is the predominately used internal hedging technique by the survey respondents. There is a significant relationship between a firm's usage of netting as an internal hedging technique and the percentage of foreign currency denominated expenses. Forward contracts are the preferred financial derivative used to hedge foreign exchange exposure. The study reveals that the manner in which firms use forward contracts is significantly influenced by their percentage of foreign currency denominated expenses. It is noted that a strategic decision with respect to management of foreign exchange risk in JSE non-financial firms falls within the purview of a firm's executive management.